Increased global arterial and subcutaneous adipose tissue inflammation in patients with moderate‐to‐severe psoriasis. (27th December 2016) - Hjuler, K.F.; Gormsen, L.C.; Vendelbo, M.H.; Egeberg, A.; Nielsen, J.; Iversen, L.
Summary: Background: Psoriasis is associated with cardiovascular disease; it has been proposed that increased cardiovascular risk is caused by low‐grade systemic inflammation involving organs and tissues other than the skin and joints. Objectives: To investigate signs of vascular inflammation in untreated patients with moderate‐to‐severe psoriasis assessed by 18 F‐fluorodeoxyglucose (FDG) positron emission tomography‐computed tomography. A secondary objective was to assess signs of subcutaneous adipose tissue inflammation. Methods: This was an observational, controlled clinical study including patients with psoriasis ( n = 12, mean ± SD age 61·4 ± 4·1 years, 83% men, mean ± SD Psoriasis Area Severity Index score 14·5 ± 4·3) and matched controls ( n = 23, mean ± SD age 60·4 ± 4·5 years, 87% men). Vascular inflammation was measured using aortic maximal standardized uptake values (SUVmax ) and the target‐to‐background ratio (TBRmax ) of the whole vessel and aortic segments. Subcutaneous adipose tissue inflammation was assessed and compared with regard to SUVmax and TBRmax . Results: Arterial inflammation was increased in patients with psoriasis vs. controls (mean ± SD whole vessel TBRmax 2·46 ± 0·31 vs. 2·09 ± 0·36; P = 0·005). In patients with psoriasis, higher FDG uptake values were observed for all aortic segments except the ascending aorta. Subcutaneous adipose tissue FDG uptake was increased in patients with psoriasis vs. controls (mean ± SD TBRmax 0·49 ± 0·18 vs. 0·31 ± 0·12; P = 0·002). Associations remained significant after adjusting for body mass index and age. Conclusions: Global arterial inflammation and subcutaneous inflammation were significantly increased in patients with moderate‐to‐severe psoriasis compared with controls. Abstract : What's already known about this topic? Psoriasis is associated with an increased risk of premature occurrence of coronary artery disease and major cardiovascular events. There is evidence of increased soluble inflammatory biomarkers in psoriasis, and imaging studies in patients with psoriasis have shown signs of vascular inflammation. Furthermore, an association between inflammation in fatty tissue in various body regions and arterial inflammation in patients with cardiovascular disease has been shown. What does this study add? Both aortic wall inflammation and inflammation in subcutaneous adipose tissue were significantly increased in patients with moderate‐to‐severe psoriasis compared with controls. These results indicate that global arterial inflammation is increased in patients with moderate‐to‐severe psoriasis and that subcutaneous adipose tissue inflammation may be a potential link between psoriasis skin inflammation, obesity and vascular inflammation. What is the translational message? This study supports the existence of a potential link between skin inflammation, obesity, vascular inflammation, systemic inflammation and cardiovascular comorbidities. The results may be taken into account in cardiovascular disease prevention in patients with psoriasis.